Pengaruh Strategi Scaffolding terhadap Penyelesaian Masalah pada Anak-anak Usia Prasekolah - Charyna Ayu Rizkyanti (Fakultas Psikologi Universitas Pancasila, 2012)
The purpose of this study was to examine the effectiveness of three different strategies (contingent, demo, dan swing) for teaching 3 to 6 years old preschool children. One experiment was done addressing issues related to preschooler's problem-solving. This study highlighted a number of functions performed by the instructor in helping the child how to master a difficult task after the instructions were given by resembling eight pieces puzzle with different shapes and colours. These strategies were derived from previous studies of four face-to-face teaching strategies by Wood, Wood, and Middleton (1978). The assumption of this study was the children taught by scaffolding or we called contingent strategy were more capable to complete the task after the instruction than two other strategies in both session instruction and post. The result showed that there was significant differences of assistance between the three strategies in both sessions, intervention session (F=20.846; p<.05) and post-intervention session (F=3.487; p<0.5). Moreover, children taught contingently demanded the least help than two other strategies and they were capable on performing the majority of the task alone. Implications of the study further suggest the importance of team work in creating successful learning process.